PERFORMANCE ANALYSIS OF I CROSS SECTION STEEL BEAM WITH A LAYER OF CFRP COATING - Prabhat Kumar; Bajaj, Rachana (Innovative Research Thoughts, 2023)
The need to reinforce structural components is universal in the modern era. Therefore, Fiber Reinforced Polymer (FRP) reinforcement seems to be a useful option for such retrofitting. While there are a number of case studies available for using FRP to reinforce concrete buildings, its application to steel presents certain challenges. Researchers have found a promising new use for the Carbon Fiber Reinforced Polymer (CFRP) in the fortification of steel structures, in particular steel beams. With advantages including high tension strength, low weight, and high strength to weight ratio, CFRP laminates are being used more often in recent years for the rehabilitation of steel I-beams. Because of its malleability and ability to take on a variety of forms, it can be easily retrofitted to a variety of constructions. A steel beam with I cross section has been considered for analysis with a dimensions of 1000 mm x 149 mm x 74 mm and a flange thickness of 6.3mm with 5.2mm thick web. The corroded steel beam has been partially coated with a layer of CFRP coating of 0.43mm thickness. 3 more different cases with a full CFRP coating of 0.43mm, 0.75 mm and 1mm thickness has been considered. It has been concluded that a 1mm full CFRP coating is the best option for reducing the risk of failure of the corroded steel beams.